Creative ecologies where thinking is a proper job - Howkins, John 1945- (New Brunswick [U.S.A.] Transaction Publishers, 2010)
In this book, the author identifies an ecology of thinking and learning based on how people create, develop and share ideas. It shows the conditions for successful thinking and learning, as well how we handle ideas and knowledge, both our own and other people's, and how this affects networks and markets.
The challenge -- First ideas -- Scope and scale -- The adaptive mind -- Creative places -- Negotiating uncertainty -- The way forward -- New places, new policies -- Three steps to growth -- The new billion.
Originally published: St Lucia, Qld. : University of Queensland Press, 2009.
Includes bibliographical references and index.
Keywords: Creative ability in business; Economics; Success in business